DOES SUSTAINABILITY REPORTING INFLUENCE FIRM PROFITABILITY? EVIDENCE FROM INDONESIA'S METALS AND MINERALS SUB-SECTOR - Rohimah; Siti Maimunah; Enok Rusmanah (Sampoerna University, 2026)
This study examines the effect of sustainability reporting, covering economic, environmental, and social disclosure, on corporate profitability, proxied by return on equity (ROE), for companies in the metals and minerals sub-sector listed on the Indonesia Stock Exchange during the 2020 to 2024 period. Employing a quantitative explanatory approach, the study applies purposive sampling and 30 firm-year observations. Panel data regression analysis is used to test the proposed relationships. The findings show that, individually, economic and environmental disclosure do not significantly influence ROE, whereas social disclosure has a positive and significant impact. However, simultaneously, the three dimensions of sustainability reporting collectively exert a positive and significant influence on profitability. These results suggest that social responsibility initiatives play a more prominent role in enhancing firm profitability. At the same time, integrated sustainability reporting contributes to overall financial performance in the metals and minerals sub-sector.